Inducible Nitric Oxide Synthase Is a Key Host Factor for Toxoplasma GRA15-Dependent Disruption of the Gamma Interferon-Induced Antiparasitic Human Response - Hironori Bando (American Society for Microbiology, 2018)
ABSTRACT Although Toxoplasma virulence mechanisms targeting gamma interferon (IFN-γ)-induced cell-autonomous antiparasitic immunity have been extensively characterized in mice, the virulence mechanisms in humans remain uncertain, partly because cell-autonomous immune responses against Toxoplasma differ markedly between mice and humans. Despite the identification of inducible nitric oxide synthase (iNOS) as an anti-Toxoplasma host factor in mice, here we show that iNOS in humans is a pro-Toxoplasma host factor that promotes the growth of the parasite. The GRA15 Toxoplasma effector-dependent disarmament of IFN-γ-induced parasite growth inhibition was evident when parasite-infected monocytes were cocultured with hepatocytes. Interleukin-1β (IL-1β), produced from monocytes in a manner dependent on GRA15 and the host’s NLRP3 inflammasome, combined with IFN-γ to strongly stimulate iNOS expression in hepatocytes; this dramatically reduced the levels of indole 2,3-dioxygenase 1 (IDO1), a critically important IFN-γ-inducible anti-Toxoplasma protein in humans, thus allowing parasite growth. Taking the data together, Toxoplasma utilizes human iNOS to antagonize IFN-γ-induced IDO1-mediated cell-autonomous immunity via its GRA15 virulence factor. IMPORTANCE Toxoplasma, an important intracellular parasite of humans and animals, causes life-threatening toxoplasmosis in immunocompromised individuals. Gamma interferon (IFN-γ) is produced in the host to inhibit the proliferation of this parasite and eventually cause its death. Unlike mouse disease models, which involve well-characterized virulence strategies that are used by Toxoplasma to suppress IFN-γ-dependent immunity, the strategies used by Toxoplasma in humans remain unclear. Here, we show that GRA15, a Toxoplasma effector protein, suppresses the IFN-γ-induced indole-2,3-dioxygenase 1-dependent antiparasite immune response in human cells. Because NLRP3-dependent production of IL-1β and nitric oxide (NO) in Toxoplasma-infected human cells is involved in the GRA15-dependent virulence mechanism, blocking NO or IL-1β production in the host could represent a novel therapeutic approach for treating human toxoplasmosis.